Solitary wave solutions for a generalized Hirota-Satsuma coupled KdV equation - Kaya, D (Elsevier Science Inc, 2004)
The solitary wave solutions of a generalized Hirota-Satsuma coupled KdV equation are obtained exactly by using the decomposition method. The solutions were calculated in the form of a convergent power series with easily computable components. A variety of initial value system is considered, the convergence of the method as applied to the coupled KdV equation is illustrated numerically. The present algorithm performs extremely well in terms of accuracy and simplicity. (C) 2002 Elsevier Inc. All rights reserved.
Keywords: the decomposition method; a generalized Hirota-Satsuma coupled KdV equation; solitary wave solutions; the tanh-function method